New taxonomical, biochronological and palaeoenvironmental data from the Middle Pleistocene site of Cúllar de Baza 1 (Granada, Spain). (1st June 2021) - Bellucci, Luca; Palombo, Maria Rita; DeMiguel, Daniel; Strani, Flavia; Alberdi, Maria Teresa
Abstract: The intra-montane Guadix-Baza Basin is one of the few continental basins in Europe that hosts a well-dated set of fossiliferous sites spanning from the latest Miocene to the late Middle Pleistocene. The Cúllar de Baza 1 (CB-1) represents a key site to investigate the effects of the Early-Middle Pleistocene Transition, considered a fundamental transformation in the Earth's climate state. Our review and update of the large mammal assemblage, and particularly equids, is of paramount relevance to understand the systematic affinities and the evolution of the Early and Middle Pleistocene European horses. We confirm the occurrence of two different taxa, the medium sized Equus altidens and the larger E. suessenbornensis . Moreover, we illustrate that CB-1 is essential for the biochronological studies of the latest Early Pleistocene/Middle Pleistocene transition (Epivillafranchian/Galerian ELMA); in particular with regard to the Last Occurrences of the Etruscan rhino Stephanorhinus etruscus and the large deer Megaloceros savini and the First Occurrence of the water-rat Arvicola mosbachensis in the Iberian peninsula. Finally, a development of a mosaic environment characterised the CB-1 site contrasting with the conditions reported for other Iberian late Early and Middle Pleistocene localities. Highlights: Cúllar Baza 1 is crucial to investigate the Early-Middle Pleistocene Transition. Equus altidens and E. suessenbornensis occurred at Cúllar Baza 1. Last Occurrence of the rhino Stephanorhinus etruscus in the Iberian peninsula. Last Occurrence of the large deer Megaloceros savini in the Iberian peninsula. Cúllar Baza 1 was characterised by a mosaic environment.